The Effects of Brand Image and Product Quality on Purchase Decisions - Rosanti, Novita; Karta Negara Salam; Panus (Yayasan Ahmar Cendekia Indonesia, 2021)
The study aim is to analyze are brand image and product quality partially positive and significant impact on purchasing decisions at Starbuck; Do brand image and product quality simultaneously have a positive and significant effect on purchasing decisions at Starbucks; Which variable has the most dominant influence on purchasing decisions at Starbucks. In this study, the authors chose the research location in Starbucks, Trans Studio Mall, Makassar City. In connection with the problems previously stated, an analysis will be carried out based on the data obtained using the following calculation: (1) Validity test, used to measure whether a questionnaire is valid or not. A questionnaire is said to be useful if the questionnaire's questions can reveal something, which is measured by the questionnaire. The results showed that the brand image variable had positive and significant influences on purchasing decisions; this indicated that Starbucks should maintain a good brand reputation, increasing consumer loyalty. Introducing products to consumers will give a good impression, and consumers will also remember the product. The results showed that the product quality variable had positive and significant effects on purchasing decisions; this indicated that Starbucks had to improve the quality of the products offered to increase sales levels. 12.9% of variables are not examined in this thesis, and this also affects the purchasing decision at Starbucks Trans Studio Mall Makassar; the variables that are not examined are (Price, Location, and Lifestyle). Researched, so you can find out what variables influence a person to make purchasing decisions at Starbucks Trans Studio Mall Makassar. In this study, the authors chose the research location in Starbucks, Trans Studio Mall, Makassar City. In connection with the problems previously stated, an analysis will be carried out based on the data obtained using the following comment: (1) Validity test, used to measure whether a questionnaire is valid or not. A questionnaire is said to be useful if the questionnaire's questions can reveal something, which is measured by the questionnaire. The results showed that the brand image variable had positive and significant effects on purchasing decisions; this indicated that Starbucks should maintain a good brand reputation, increasing consumer loyalty. Introducing products to consumers will give a good impression, and consumers will also remember the product. The results showed that the product quality variable had positive and significant influences on purchasing decisions; this indicated that Starbucks had to improve the quality of the products offered to increase sales levels. 12.9% of variables are not examined in this thesis, and this also affects the purchasing decision at Starbucks Trans Studio Mall Makassar, the variables that are not examined are (Price, Location, and Lifestyle). Researched, so you can find out what variables influence a person to make purchasing decisions at Starbucks Trans Studio Mall Makassar.